Beyond the Liquidity Illusion: Evaluating the Efficiency of Indonesia’s Himbara Banks - Pamungkas, Binar Dwiyanto; Ratnawati, Tri; Khairunnisah, Noni Antika (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Analyze the efficiency levels of Himbara banks after receiving Rp200 trillion in funds from the Ministry of Finance. Compare the efficiency levels between Himbara banks in the periods before and after the fund placement policy. Identify internal factors that influence the efficiency of government fund management at Himbara banks. This study uses a quantitative approach with the non-parametric Data Envelopment Analysis (DEA) method. This approach was chosen because it can measure the relative efficiency between decision-making units (DMUs) without requiring specific production function assumptions (Charnes, Cooper, & Rhodes, 1978). DEA allows researchers to evaluate the ability of Himbara banks to efficiently convert inputs (resources) into outputs (intermediation results). The analysis was conducted for the period 2024–2025, covering conditions before and after the placement of IDR 200 trillion in funds from the Ministry of Finance. To analyze factors influencing efficiency, the Tobit regression model was used. Data Envelopment Analysis (DEA) results show that the Rp200 trillion injection of funds was only effective in increasing efficiency at already productive banks (BRI, Mandiri, and BTN), while BNI still exhibited inefficiency due to its inability to convert additional funds into proportional credit growth and interest income. This indicates the need for improvements in credit distribution strategies, operational cost management, and risk management so that the injection of public funds truly has an optimal impact on efficiency and economic growth. Tobit Regression results indicate that bank efficiency in Indonesia tends to increase if banks have strong capital adequacy, good asset quality, and optimal intermediation capabilities. Conversely, increasing NPLs and excessive asset expansion can be factors that reduce efficiency. Therefore, future banking policy strategies need to focus on improving asset quality, cost efficiency, and implementing effective governance across all bank scales